62‐5: Efficient On‐Chip Quantum‐Rod LED with Supreme Stability for Display and Lighting Application. Issue 1 (28th June 2021) - KANG, C.; Prodanov, M.F.; GAO, Y.; Mallem, K.; Chaudhari, P.; Valerii, V.; SRIVASTAVA, A.K.
Abstract : The down‐conversion materials with an on‐chip design for display backlight have brought lots of attention due to their high performance and low material cost. However, it still suffers from high optical and thermal flux degradation. FRET in closely packaged film limits the overall efficiency. In this paper, we present white LEDs by printing thermally stable CdSe/ZnxCdl‐xS quantum rods (QRs) as a luminescent down convertor on the Blue LED chip. Thus, fabricated LEDs offer high luminescence efficacy (∼98 lm/W) and a saturated colors gamut of 118% NTSC (∼90% of BT2020) for displays. Furthermore, the amount of cadmium in the QRs is reduced significantly. Thus, these QR based LEDs are highly suitable for display backlighting and lighting applications.